Intraspecies Genomic Divergence of a Fig Wasp Species Is Due to Geographical Barrier and Adaptation - Xu, Xun; Wang, Bao-Sheng; Yu, Hui (Frontiers in Ecology and Evolution, 2021)
Understanding how intraspecies divergence results in speciation has great importance for our knowledge of evolutionary biology. Here we applied population genomics approaches to a fig wasp species (Valisia sp1) to reveal its intraspecies differentiation and the underlying evolutionary dynamics. With re-sequencing data, we prove the Hainan island population (DA) of sp1 genetically differ from the continental ones, then reveal the differed divergence pattern. DA has reduced SNP diversity but higher proportion of population-specific structural variations (SVs), implying a restricted gene exchange. 32 differentiated islands containing 204 genes were detected based on SNPs, along with 1,532 population-specific SVs of DA overlapping 4,141 genes. The gene ontology (GO) enrichment analysis performed on differentiated islands linked to 3 significant GO terms on basic metabolism process, with most of the genes fail to enrich. In contrary, population-specific SVs contributed more to the adaptation than the SNPs by linking to 59 terms that are crucial for wasp speciation, such as host reorganization and development regulation. Besides, the generalized dissimilarity modelling confirms the importance of environment difference on the genetic divergence within sp1 . Hence we assume the genetic divergence between DA and the continent due to not only the strait as a geographic barrier, but also adaptation. We reconstruct the demographic history within sp1 . DA shares a similar population history with the nearby continental population, suggesting a incomplete divergence. Summarily, our results reveal how geographic barrier and adaptation both influent the genetic divergence at population-level, increase our knowledge on the potential speciation of non-model organism.